Sex steroid hormones differentially regulate CYP2D in female wild-type and CYP2D6-humanized mice. Issue 2 (May 2020) - Konstandi, Maria; Andriopoulou, Christina E; Cheng, Jie; Gonzalez, Frank J
Abstract : The CYP2D subfamily catalyses the metabolism of about 25% of prescribed drugs, including the majority of antidepressants and antipsychotics. At present, the mechanism of hepatic CYP2D regulation remains largely unknown. This study investigated the role of sex steroid hormones in CYP2D regulation. For this purpose, Cyp2d22 expression was assessed in the distinct phases of the estrous cycle of normocyclic C57BL/6J (WT) female mice. Cyp2d22 was also evaluated in ovariectomised WT and CYP2D6-humanized (hCYP2D6) mice that received hormonal supplementation with either 17β-estradiol (E2) and/or progesterone. Comparisons were also made to male mice. The data revealed that hepatic Cyp2d22 mRNA, protein and activity levels were higher at estrous compared to the other phases of the estrous cycle and that ovariectomy repressed Cyp2d22 expression in WT mice. Tamoxifen, an anti-estrogenic compound, also repressed hepatic Cyp2d22 via activation of GH/STAT5b and PI3k/AKT signaling pathways. Both hormones prevented the ovariectomy-mediated Cyp2d22 repression. In case of progesterone, this may be mediated by inhibition of the PI3k/AKT/FOX01 pathway. Notably, Cyp2d22 mRNA levels in WT males were similar to those in ovariectomised mice and were markedly lower compared to females at estrous, a differentiation potentially regulated by the GH/STAT5b pathway. Sex steroid hormone-related alterations in Cyp2d22 mRNA expression were highly correlated with Hnf1a mRNA. Interestingly, fluctuations in Cyp2d22 in hippocampus and cerebellum followed those in liver. In contrast to WT mice, ovariectomy induced hepatic CYP2D6 expression in hCYP2D6 mice, whereas E2 and/or progesterone prevented this induction. Apparently, sex steroid hormones display a significant gender- and species-specific role in the regulation of CYP2D.